Employee Productivity in the Palm Oil Industry: The Role of Vertical Communication, Work Discipline, and Intrinsic Motivation - Abd Fatah Dafhi Putra Wendi; Abd. Rasyid Syamsuri; Prima Andreas (International Journal of Science and Environment (IJSE), 2026)
This study aims to examine the effect of vertical communication, work discipline, and intrinsic motivation on employee productivity at PT. Eka Dura Indonesia, Rokan Hulu Regency, Riau. This research employed a quantitative approach using a survey method. The population consisted of 118 field employees, and total sampling was applied, resulting in 118 respondents. Data were analyzed using multiple linear regression assisted by SmartPLS 4 software. The findings reveal that vertical communication, work discipline, and intrinsic motivation have positive and significant effects on employee productivity, both partially and simultaneously. Among the independent variables, work discipline demonstrated the strongest influence on employee productivity. The coefficient of determination (R²) showed that 73.9% of employee productivity could be explained by the three independent variables, while the remaining 26.1% was influenced by other factors outside the model. These findings highlight the importance of effective communication, discipline, and intrinsic motivation in improving employee productivity within the palm oil industry.